Perinatal consequences of childbirth in pregnant women with a history of reproductive losses - Solovіova, N. M.; Siusiuka, V. H.; Соловйова, Н. М.; Сюсюка, Володимир Григорович (My University, 2024)
The aim of this study was to assess the frequency and structure of perinatal consequences of childbirth in pregnant women with a history of reproductive loss. A retrospective analysis of exchange cards of pregnant women, histories of pregnancy and childbirth, newborn cards of 130 women who were registered in women's consultations in the city of Zaporizhzhia and gave birth in the maternity hospital № 9 in the period 2017-2020. Women were divided into 2 groups depending on obstetric history. The main group consisted of 85 women with one reproductive loss in the anamnesis, the control group - 45 women without a reproductive loss in the anamnesis. Childbirth was the first in 40 women (47,1%) of the main group and in 26 women (57,8%) from the control group. The research meets the modern requirements of moral and ethical norms regarding the rules of ICH / GCP, the Declaration of Helsinki (1964), the Conference of the Council of Europe on Human Rights and Biomedicine, as well as the current provisions of the legislative acts of Ukraine. The chosen direction of research is closely related to the plan of research work of the Department of Obstetrics and Gynecology of the Zaporizhzhya State Medical and Pharmaceutical University. Variational and statistical processing of the results was carried out using the "STATISTICA 13" program. Метою даного дослідження було оцінити частоту та структуру перинатальних наслідків розродження у вагітних жінок з репродуктивною втратою в анамнезі. Було проведено ретроспективний аналіз обмінних карт вагітних, історій вагітності та пологів 130 жінок, які перебували на обліку в жіночих консультаціях м. Запоріжжя та народжували в КНП «Пологовий будинок №9» ЗМР та 130 карт новонароджених в період 2017-2020 рр. Жінки були поділені на 2 групи залежно від акушерського анамнезу. Основну групу склали 85 жінок з однією репродуктивною втратою в анамнезі, контрольну – 45 жінок без репродуктивної втрати в анамнезі. Пологи були першими у 40 жінок (47,1% ) основної групи та у 26 жінок (57,8 %) з групи контролю. Дослідження відповідає сучасним вимогам морально-етичних норм щодо правил ICH / GCP, Гельсінкській декларації (1964 року), Конференції Ради Європи про права людини і біомедицини, а також діючим положенням законодавчих актів України. Обраний напрямок дослідження тісно пов`язаний з планом науково- дослідної роботи кафедри акушерства і гінекології Запорізького державного медико-фармацевтичного університету. Варіаційно-статистична обробка результатів здійснювалась з використанням програми «STATISTICA 13».
Перинатальні наслідки розродження вагітних жінок з репродуктивною втратою в анамнезі
Keywords: pregnancy; reproductive loss in history; childbirth; perinatal complications; pathological condition; early neonatal period; вагітність; репродуктивна втрата в анамнезі; пологи; перинатальні ускладнення; патологічний стан; ранній неонатальний період